KEPENTINGAN INDONESIA IKUT SERTA DALAM KERJASAMA INDOMALPHIL TERHADAP PEMBERANTASAN KEJAHATAN ABU SAYYAF TAHUN 2016-2018 - Razululul Azmi; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The problem of piracy accompained from the cases of hostage taking by asking for ransoms that made by the Abu Sayyaf Group in the Sulawesi-Sulu Sea, it caused a serious concern for some contries such as Indonesia, Malaysia and Philipinnes. Indonesia as one of the victims of this piracy ships action was tried to take the steps reorganzie the regional security. The initiation finally found the win-win solution, and the three countries was agreed to meet and discuss this serious problem. Which is, in the end the meeting was beginning of the formation of the three state cooperation. The method of data collecting is done by collecting primer data, then analyzed in qualitative to obtain the draft about the main problem. The method of this research is the method of qualitative explanatif. The data is obtained through primer data such as direct interview via e-mail and chatiing to relevant agencies, and the data is obtained secunder data such as book, journal, newspaper and website. From the result of research, that trilateral cooperation initiated by Indonesia as a form of security arrangement in the Sulawesi-Sulu Sea is inseparable from the national interests thats Indonesia wants to protect and achieve. These interests consist of defense, economic, and ideological interests. Trilateral cooperation is well implemented, has minimized cases of piracy and robbery againts ship the next year.Keywords: Indonesia, National Interest, Trilateral Cooperation, Abu Sayyaf, Sulawesi-Sulu Sea.